“Against a tyrant” and “for a tyrannicide”. Rhetoric paideía and political action in Cicero - Leorza, María José (De Rebus Antiquis, 2018)
The present paper studies the greco-latin “rhetoric paideia” in Cicero’s Pro Milone. In this forensic speech we analyse the presence of a structure similar to the one of the school exercise of rethorical education koinós topos or “common topics”. We identify the following themes: “against a tyrant” and “for a tyrannicide”, distinctive of the progymnasma. These themes add to the composition of the figures of the tyrant and the tyrannicide. We claim that both figures are a rhetorical and a political construction made by Cicero and that they mould the practice of a particular political action in the public life of the Roman Late Republic: the tyrannicide